Captain Wag and big blue whale - Terry, Michael (London : Bloomsbury, 2008)
Captain Wag is a pirate dog and his friends, one-eye Jack and Old Sccratch, are marooned! How can they escape fromtheir lonely treasure island, escape the clutches of their way home? With a little ingenuity and a lot of unexpected help, that's how.
Keywords: Pirates -- Fiction; Sailing -- Fictions; Whales -- Fiction